Research and development issues prioritization for vegetable seeds in India: A perception study - ROY, SHUBHADEEP; GUPTA, NAKUL; SINGH, NEERAJ; C, MANIMURUGAN; SINGH, P M; SINGH, JAGDISH (The Indian Journal of Agricultural Sciences, 2021)
Seed is recognized to be the cheapest source, yet most critical single input for enhancing vegetable productivity. Use of good quality seeds can result in 15-20% yield increase. The Indian vegetable seed sector is established with tremendous potential to grow beyond boundaries of domestic market. Being high value per unit weight, vegetable seed segment has a significant share in the overall seed market in monetary terms. Although the price of vegetable seeds in market is very high, farmers are facing problem of spurious seed, low germination percentage and unavailability of quality seeds on time. Research and development interventions are required to overcome these problems and an effort has been made to identify the priority areas where interventions are required in vegetable seed sector. This study was undertaken during 2014-16 by conducting a survey of vegetable and seed experts in which major constraints in vegetable seed sector were identified. The constraints are rank ordered as perceived by the respondents like exorbitantly high price of private sector hybrids (Score-680, Rank-1), unavailability of quality seeds of recommended/released hybrids and OP varieties of vegetables (Score-658, Rank-2) and many more which have been discussed and will draw attention on the issues related to the vegetable seed sector which needs priority in further research.